Commodity Substitution in Plantation Communities in Sandana Village - Abdul Rahman (CV. ULIL ALBAB CORP, 2026)
Substitute commodities are substitute products with the same utility value as a company's previous products. Most businesses generally include the procurement of these materials in their marketing plans to optimize sales. The definition of substitute commodities can also be understood as an option or solution when a company runs out of stock of a particular product during times of high market demand. Of course, the decision to transact these materials is left to the consumer. This study aims to identify the driving factors behind commodity substitution in Sandana Village. The method used was qualitative research through observation, interviews, and documentation. The results indicate that the factors driving farmers' decisions to switch to oil palm are supported by a combination of economic factors and external support. In addition to the potential for higher profits, the presence of viruses or pests on previous crops is also a factor.